Penafsiran Ayat-Ayat al-Qur’an tentang Kejujuran - Amiroliyanti Amiroliyanti; Syafira Al-Alya. H (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Honesty is a very important trait in Islam and is also one of the characteristics that every Muslim should possess. Honesty means telling the truth as it really is and not lying, either in word or in action. In Islam, honesty is considered one of the most noble and praiseworthy traits. Allah SWT says in the Qur'an, “If you speak, then speak truthfully, even if it hurts.” (QS. Al-Ahzab: 70). Honesty has many benefits, both in personal life and in social life. With honesty, we can build trust and good relationships with others, and maintain our integrity and dignity. Due to the rapid development of technology and relationships spread all over the world, there is a tendency to ignore fairness to achieve personal goals or ignore honesty to gain quick profits. Under these circumstances, the values of fairness and honesty found in the Qur'an become more necessary to implement in life. By using a thematic approach to related verses. This research aims to gain a deeper understanding of the concept of honesty in the context of Al-Qur'an interpretation.